Education for the future? Critical evaluation of education for sustainable development goals - Kopnina, Helen (The Journal of environmental education, 2020)
Building on the Millennium Development Goals, Education for Sustainable Development (ESD) and Education for Sustainable Development Goals (ESDG) were established. Despite the willingness of many educational institutions worldwide to embrace the SDGs, given escalating sustainability challenges, this article questions whether ESDG is desirable as "an education for the future". Many challenges outlined by the SDGs are supposed to be solved by "inclusive" or "sustainable" economic growth, assuming that economic growth can be conveniently decoupled from resource consumption. Yet, the current hegemony of the sustainability-through-growth paradigm has actually increased inequalities and pressure on natural resources, exacerbating biodiversity loss, climate change and resulting social tensions. With unreflective support for growth, far from challenging the status quo, the SDGs and consequently, the ESDGs, condone continuing environmental exploitation, depriving millions of species of their right to flourish, and impoverishing future generations. This article creates greater awareness of the paradoxes of sustainable development and encourages teaching for sustainability through various examples of alternative education that emphasizes planetary ethic and degrowth. The alternatives include Indigenous learning, ecopedagogy, ecocentric education, education for steady-state and circular economy, empowerment and liberation.